ANCIENT URBAN CIVILIZATIONS OF CENTRAL ASIA AND THEIR CONTEMPORARY SIGNIFICANCE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article analyzes the historical development of ancient urban civilizations formed in Central Asia and their significance in modern society based on scientific sources and archaeological research. The study examines the emergence of ancient cities such as Samarkand, Bukhara, Khorezm, Termez, and Merv, their economic development, roles in trade relations, and importance as centers of science and culture. Archaeological excavations and historical written sources demonstrate that developed irrigation systems, craft production, and trade infrastructure had already been formed in these regions from pre-Christian times.